In context : the Reade festschrift - Finkel, Irving L.; Simpson, St John; Reade, Julian (Archaeopress Archaeology, 2020)
A collection of invited and peer-reviewed essays by friends and colleagues of Julian Edgeworth Reade, sometime Mesopotamia curator at the British Museum from 1975 to 2000. Here is fresh work from which any reader can gain a new appreciation of the importance of the ancient Near East.